2010
DOI: 10.1021/jf904087n
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Solvent Extraction of Anthocyanins from Dried Red Grape Pomace

Abstract: Accelerated solvent extraction (ASE) was used to optimize and determine the effectiveness of an alternative, environmentally friendly extraction procedure using subcritical solvents to recover anthocyanins from freeze-dried, ground Sunbelt red grape pomace. Anthocyanins were extracted from pomace using the following ASE variables: pressure (6.8 MPa), one extraction cycle, and temperature (40, 60, 80, 100, 120, and 140 degrees C). Conventional solvent extraction with methanol/water/formic acid (60:37:3 v/v/v) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
92
0
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 33 publications
10
92
0
11
Order By: Relevance
“…Extraction of target compounds from grape pomace is mainly affected by grape variety/ vintage, type of extraction/solvent, acidity, temperature, time, addition of enzymes, and particle size [14][15][16][17][18][19][20] . Ethanol is generally recognized as safe (GRAS status), and is commonly used as organic solvent in conventional extraction of polyphenols 21 . Increased temperature improves extraction due to better diffusion and disruption of plant cellular structures 14,21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of target compounds from grape pomace is mainly affected by grape variety/ vintage, type of extraction/solvent, acidity, temperature, time, addition of enzymes, and particle size [14][15][16][17][18][19][20] . Ethanol is generally recognized as safe (GRAS status), and is commonly used as organic solvent in conventional extraction of polyphenols 21 . Increased temperature improves extraction due to better diffusion and disruption of plant cellular structures 14,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol is generally recognized as safe (GRAS status), and is commonly used as organic solvent in conventional extraction of polyphenols 21 . Increased temperature improves extraction due to better diffusion and disruption of plant cellular structures 14,21 . Increased acidity induced by the use of strong acids, such as HCl, with elevated temperatures, tends to shorten the extraction time of polyphenols (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These studies also indicated the possibility of thermal degradation of the target solutes occurring at higher temperatures. Srinivas et al (2009) Monrad et al (2010) and plotted in Figure 1. Fig.…”
Section: Predicting Solubility Via the Hansen Solubility Parametermentioning
confidence: 99%
“…1. Concentration of recovered Malvidin-3,5-O-diglucoside in hydroalcoholic extracts from subcritical extraction (Data from Monrad et al, 2010).…”
Section: Predicting Solubility Via the Hansen Solubility Parametermentioning
confidence: 99%
“…These include extraction methods of fractioned high speed pressure from elderberry pomace (Saebra et al, 2010), subcritical solvent from dried grape pomace (Monrad et al, 2010), and ultrasound-assisted from Garcinia indica Choisy (Nayak and Rastogi, 2013). Despite the different methods, solvent extraction of anthocyanins from plant materials is the most widely employed method and has been well documented in two standard protocols.…”
Section: Introductionmentioning
confidence: 99%